Design an X-Band frequency synthesizer - Ameri Mahabadi, H.; Attaran, A.; Moghavvemi, M. (2010)
This frequency synthesizer design aims at achieving low phase and high reliability for X-band digital microwave radio applications, using a commercial device and frequency tripling techniques.